"Welcome to Divinity College": Subjectification in Pilgrimage to the Iran-Iraq War Battlefields in Contemporary Iran. Issue 1 (1st June 2020) - Zandi, Mahshid
Abstract: "Welcome to Divinity College, " reads a welcome sign to the state-sponsored fieldtrips of the Iran-Iraq War (1980–1988) battlefields in Iran. Rahian-e Noor battlefield tours follow the model of Shia pilgrimage and commemorative rituals, while also tapping into nationalist discourses of the country as an ancient homeland. I ask whether these trips are a means of disseminating knowledge, and what forms of ignorance are assumed to prevail among the visitors that this "Divinity College" seeks to eliminate? Even more importantly, since the tours are state-sponsored, what ignorances are rendered possible, if not encouraged, at the cost of this selective knowledge dissemination? Drawing on fieldwork, I argue that the tours provide a space of encounter with what is presupposed as the visitors' already acquired knowledge. On RN tours, both knowledge and ignorance are co-constitutive of the transformative power of pilgrimage, where ultimate knowledge is interpreted as putting the already-known-words into deeds.